Genetic and Mitochondrial Metabolic Analyses of an Atypical Form of Leigh Syndrome - Uittenbogaard, Martine; Sen, Kuntal; Whitehead, Matthew; Brantner, Christine A.; Wang, Yue; Wong, Lee-Jun; Gropman, Andrea; Chiaramello, Anne (Frontiers in Cell and Developmental Biology, 2021)
In this study, we aimed to establish the mitochondrial etiology of the proband’s progressive neurodegenerative disease suggestive of an atypical Leigh syndrome, by determining the proband’s pathogenic variants. Brain MRI showed a constellation of multifocal temporally disparate lesions in the cerebral deep gray nuclei, brainstem, cerebellum, spinal cord along with rhombencephalic atrophy, and optic nerve atrophy. Single voxel 1H MRS performed concurrently over the left cerebral deep gray nuclei showed a small lactate peak, increased glutamate and citrate elevation, elevating suspicion of a mitochondrial etiology. Whole exome sequencing revealed three heterozygous nuclear variants mapping in three distinct genes known to cause Leigh syndrome. Our mitochondrial bioenergetic investigations revealed an impaired mitochondrial energy metabolism. The proband’s overall ATP deficit is further intensified by an ineffective metabolic reprogramming between oxidative phosphorylation and glycolysis. The deficient metabolic adaptability and global energy deficit correlate with the proband’s neurological symptoms congruent with an atypical Leigh syndrome. In conclusion, our study provides much needed insights to support the development of molecular diagnostic and therapeutic strategies for atypical Leigh syndrome.